Intensifying Haze and Disappearing Dense Fog in Winter at Tribhuvan International Airport, Kathmandu: Impacts in Aviation - Kathayat, Bhogendra; Panday, Arnico Kumar; Pokharel, Binod; Chapagain, Narayan Prasad (Journal of Institute of Science and Technology, 2024)
In winter, Tribhuvan International Airport (TIA) in Kathmandu, Nepal, is badly affected by poor visibility conditions due to the occurrence of thick haze and dense fog. In this study, we examined the microclimatic behaviors (e.g., consecutive duration and onset/dispersal) of the winter fog. Alongside, we analyzed the trend in the occurrence of fog, dense fog, and winter haze in TIA from a historic global hourly climatological dataset (1976–2022) from TIA. We found that radiation fog in the valley is mostly short spells having a consecutive duration of less than an hour ( 86% of fog, 95% of dense fog). The onset of fog starts most favorably in the early morning (05:45–09:00 am) and disperses mostly before noon. To ascertain the synergetic effect of enhanced natural and anthropogenic forcing, urbanization, and meteorological changes on winter haze and fog, we assessed their trend for the same period. There was a marked change in visibility around the year 2000 together with important changes in humidity and dew point depression. We observed an upward trend of winter haze frequency (2.36% day/year, at 0.001 level of significance (α)) and fog frequency (0.46% day/year, at α = 0.05) in regime-I (1976–2000). Whereas the trend of winter haze flattened to 0.36% day/year (at α = 0.05) and dense fog declined at the rate of 1.28% day per annum (at α = 0.01) in regime-II (2001–2022). By careful examination of all plausible climatological drivers of the change (relative humidity, temperature, wind speed, and dew point depression), we found strong evidence of decreasing humidity and increasing dew point depression after the year 2000. Effective air pollution and urbanization control measures are imminent to lessen the adverse impact of the increased frequency of haze and fog at the country’s major international airport, TIA.